PARENTING EDUCATION DALAM PENCEGAHAN STUNTING DI DESA WIBAWAMULYA - Badriah, Siti; Arrahman, Zahra Kusumaningati; Andini, Rosa; Nurhidayah, Siti (An-Nizam, 2025)
Stunting is a health problem caused by chronic malnutrition and affects the physical growth and cognitive development of children. The main factors that contribute to stunting include parents' lack of understanding about balanced nutrition, socioeconomic conditions, and a less supportive environment. Therefore, stunting prevention efforts need to be carried out through an effective educational approach, one of which is through a parenting education program. This counseling activity was carried out in Wibawamulya Village with the aim of increasing parents' knowledge and awareness about the importance of appropriate nutritional intake for children. The program involved posyandu cadres and the Wibawamulya Village Midwife as the main facilitators, with support from the UNISMA Bekasi KKN Group 5 Team. The methods used included socialization and interactive counseling on parenting patterns that support children's optimal growth. The results showed an increase in parents' understanding of healthy eating patterns and the importance of regular monitoring of children's growth and development. It is hoped that through this approach, stunting cases can be minimized, and the quality of health of children in Wibawamulya Village can be significantly improved.